2020
DOI: 10.1073/pnas.1916725117
|View full text |Cite
|
Sign up to set email alerts
|

Two systems for thinking about others’ thoughts in the developing brain

Abstract: Human social interaction crucially relies on the ability to infer what other people think. Referred to as Theory of Mind (ToM), this ability has long been argued to emerge around 4 y of age when children start passing traditional verbal ToM tasks. This developmental dogma has recently been questioned by nonverbal ToM tasks passed by infants younger than 2 y of age. How do young children solve these tests, and what is their relation to the later-developing verbal ToM reasoning? Are there two different systems f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 59 publications
4
47
0
1
Order By: Relevance
“…For example, Richardson et al 55 using fMRI show that in typically developing children (3-12 years) the ability to solve cognitive ToM tasks relies on the same brain network recruited when adults reason about others' mental states (i.e., medial prefrontal cortex, temporoparietal junction, and precuneus) and that over time this network gradually becomes more integrated and distinct from other networks. More importantly, combining white matter measures acquired by means of tract-based spatial statistics and probabilistic tractography with behavioural performance in false belief tasks, it has been recently demonstrated that the developmental breakthrough in false belief understanding in 3-and 4-year-old children is associated with age-related changes in local white matter structure in temporoparietal regions, the precuneus and medial prefrontal cortex, and that these effects are independent of co-developing EFs 29,56 . As suggested by Grosse Wiesmann et al 56 , these findings are inconsistent with the view that young children only fail explicit ToM tasks due to extrinsic executive demands of these tasks because, in that case, brain regions involved in EFs should be related to success in the tasks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Richardson et al 55 using fMRI show that in typically developing children (3-12 years) the ability to solve cognitive ToM tasks relies on the same brain network recruited when adults reason about others' mental states (i.e., medial prefrontal cortex, temporoparietal junction, and precuneus) and that over time this network gradually becomes more integrated and distinct from other networks. More importantly, combining white matter measures acquired by means of tract-based spatial statistics and probabilistic tractography with behavioural performance in false belief tasks, it has been recently demonstrated that the developmental breakthrough in false belief understanding in 3-and 4-year-old children is associated with age-related changes in local white matter structure in temporoparietal regions, the precuneus and medial prefrontal cortex, and that these effects are independent of co-developing EFs 29,56 . As suggested by Grosse Wiesmann et al 56 , these findings are inconsistent with the view that young children only fail explicit ToM tasks due to extrinsic executive demands of these tasks because, in that case, brain regions involved in EFs should be related to success in the tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, and in accord with previous research, verbal skills did not relate to performance on this task in contrast to the well-established link between explicit false belief tasks and language [ 73 ]. Furthermore, performance on implicit and explicit theory of mind tasks in childhood did not converge, suggesting that distinct cognitive processes underlie implicit and explicit false belief reasoning, as recently confirmed in a study showing dissociated brain regions involved in processing implicit and explicit false belief tasks [ 74 ]. The results are therefore compatible with a dual process view of implicit and explicit ToM which suggests an automatic, cognitively efficient (possibly unconscious) belief-tracking system already present in infancy, and an explicit more flexible but cognitively more demanding belief processing system, which develops later [ 12 , 29 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 92%
“…To obtain measures of cortical thickness and surface area, we used the preprocessed brain images from a recent study using the current dataset (Grosse Wiesmann et al, 2020 (Fischl & Dale, 2000). Surface area of the GM/WM boundary and cortical thickness, defined as the closest distance from the GM/WM boundary to the GM/CSF boundary, was calculated at each vertex.…”
Section: Cortical Surface-based Analysesmentioning
confidence: 99%